Interrelation of cardiovascular diseases with anaerobic bacteria of subgingival biofilm - Elena Nikolaevna Nikolaeva; Viktor Nikolaevich Tsarev; Tatyana Viktorovna Tsareva; Evgenii Valeryevich Ippolitov; Sergey Darchoevich Arutyunov (Wolters Kluwer Medknow Publications, 2019)
Aims: The aim of this study is to study the colonization of subgingival biofilm (SGB) with periodontopathogenic bacteria species and endothelium-dependent vasodilation in patients with coronary heart disease and concomitant periodontitis. Subjects and Methods: Forty-five patients with cardiovascular diseases (CVDs) were examined - 28 women (62%) and 17 men (38%) aged 53-76 years, including 15 patients with acute myocardial infarction (AMI), 15 patients with exertional angina (pectoris), and 15 patients with chronic periodontitis (CP) without CVD. Dental and cardiological health conditions were determined, a biochemical blood test was conducted, endothelium-dependent vasodilation in the brachial artery was measured, and DNA of periodontopathogenic bacteria in SGB was detected. Results: A reliable interrelation between the colonization of SGB with periodontopathogenic bacteria and development of AMI was established. In AMI patients, the frequency of Porphyromonas gingivalis, Tannerella forsythia, and Aggregatibacter actinomycetemcomitans detection was significantly higher than in the group of participants without cardiovascular disease. The presence of P. gingivalis and A. actinomycetemcomitans in patients with CP directly correlated with severity of periodontal tissue destruction. Endothelium-dependent vasodilation in the brachial artery moderately correlated with patient's cardiological condition (r = 0.3284), biochemical markers of atherosclerosis development (r = 0.6465), and frequency of P. intermedia detection in periodontal pockets (r = 0.3828). Conclusions: Periodontal status in patients with AMI is characterized by unsatisfactory and poor hygiene, increased indices of bleeding on probing, and periodontal pocket depth in comparison to groups of patients with angina pectoris and CP without cardiovascular pathology.